원어민 코퍼스와 고등학교 영어 교과서에 나타난 강조 부사 very의 패턴 비교 - 한계수; 김현옥 (Foreign Languages Education, 2019)
This study investigated the use of the amplifier very in high school English textbooks and native corpora by comparing its frequency distributions and collocation patterns. The native corpora, used as the reference of the study, were COCA and BNC, with their built-in sub-corpora further grouped into spoken and written corpora. The High School English Textbook Corpus (HSETC) was compiled from a total of 53 high school textbooks, with the spoken corpus (HSETC-S) from the texts in listening and conversation and the written corpus (HSETC-W) from the reading passages. Analyses using AntConc3.4.4 revealed no prominent differences between HSETC and reference corpora in the frequency of the amplifier very, while the written corpus (HSETC-W) had more occurrences contrary to the native corpora. The combination patterns and their occurrences of HSETC were slightly different from those of COCA and BNC with the gap increased with the spoken corpus (HSETC-S). Pedagogical implications and suggestions are made on ELT materials development and teaching practices.
Keywords: 코퍼스 분석; 연어; very; 교과서; 원어민 코퍼스; corpus analysis; collocation; very; textbooks; native corpora